Wheelchair basketball, health, competitive analysis, and performance advantage: a review of theory and evidence - Najafabadi, M. G.; Shariat, A.; Anastasio, A. T.; Khah, A. S.; Shaw, I.; Kavianpour, M. (Journal of Exercise Rehabilitation, 2023)
The purpose of this study was to review the various risks and benefits of wheelchair basketball (WB) and explore some of the research which outlines factors that influence WB player performance and conditioning. WB offers several physical and psychological advantages. Physically, it can improve muscle strength, endurance, and cardiovascular fitness while decreasing the prevalence of chronic physical disorders. From a psychological standpoint, WB has been shown to alleviate anxiety and feelings of depression while also creating and improving social relationships. Despite the many benefits, WB can cause injuries, particularly in the upper extremities, and preventative measures should be employed. WB necessitates intense intermittent efforts and athletes must maintain excellent cardiovascular fitness, strength, and muscular endurance. Healthy sleeping patterns have also been shown to improve performance in WB players. Wheelchair mobility and biomechanical variables as well as wheelchair size and weight appear to be critical success elements in WB. WB can be a powerful tool for coaches and therapists to boost the physical and emotional health of individuals with disabilities and motivate them to participate in team-based sport.